2022
DOI: 10.3389/fnut.2022.1007506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic extract on weight loss and gut microbiota composition in obese women: A double-blind randomized controlled trial

Abstract: ObjectiveFrom a nutritional perspective, garlic extract could be a prebiotic product, which is useful for obese subjects, and one of its health-promoting underlying mechanisms is modulating gut microbiota composition. In this randomized double-blind clinical trial, the goal was to determine the effect of Allium (garlic extract) on anthropometric indices and gut microbiota composition in obese women following a low-calorie diet.Materials and methodsForty-three obese women were randomly divided into garlic extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The probiotic species used, L. mesenteroides is known to produce exopolysaccarides which display prebiotic properties ( Pan et al, 2020 ; Miyamoto et al, 2023 ) whereas garlic was previously reported as a rich source of fructans (70%–80% of dry weight) which also have proven prebiotic potential ( Lu et al, 2021 ). In the human gut, studies have shown an increased abundance of bacteria belonging to the Faecalibacterium ( Panyod et al, 2022 ) and Bifidobacterium ( Ettehad-Marvasti et al, 2022 ) genera in the presence of fructans. Therefore, it is possible that garlic aqueous extract has an additive or synergistic role in influencing changes in the microbiome when used in combination with L. mesenteroides.…”
Section: Resultsmentioning
confidence: 99%
“…The probiotic species used, L. mesenteroides is known to produce exopolysaccarides which display prebiotic properties ( Pan et al, 2020 ; Miyamoto et al, 2023 ) whereas garlic was previously reported as a rich source of fructans (70%–80% of dry weight) which also have proven prebiotic potential ( Lu et al, 2021 ). In the human gut, studies have shown an increased abundance of bacteria belonging to the Faecalibacterium ( Panyod et al, 2022 ) and Bifidobacterium ( Ettehad-Marvasti et al, 2022 ) genera in the presence of fructans. Therefore, it is possible that garlic aqueous extract has an additive or synergistic role in influencing changes in the microbiome when used in combination with L. mesenteroides.…”
Section: Resultsmentioning
confidence: 99%
“…The results of clinical studies on garlic extracts are controversial. In a very recent double‐blind clinical trial, 43 obese women were randomized to receive two garlic extract tablets (400 mg, containing 1.1 μg of allicin per tablet) or placebo per day (Ettehad‐Marvasti et al, 2022). At the end of the 2‐month intervention period, both placebo and garlic extract reduced BMI (by 2.7% and 1.7%, respectively), body weight, hip and waist circumference in obese women.…”
Section: Effects Of Alliaceae and Brassicaceae On Anthropometric Para...mentioning
confidence: 99%